Syed Sheikh al-Hadi’s Views on the Educational Reforms in Malaya - Akgun, Tayfun; Zakariya, Hafiz (UKM Press, 2019)
Though there is a growing body of literature on Syed Sheikh al-Hadi, few focuses on his contributions to the educational reform. Thus, this study analyzes Syed Sheikh al-Hadi’s views on the educational reforms. Al-Hadi who epitomized the Malay reformists was discontent with the traditional Islamic education in Malaya because of its inadequacy to prepare the future generation to meet the challenges of modernity. For this purpose, al-Hadi emphasized the reform of Islamic education system through the madrasah, which would offer both the religious and secular subjects. Further, al-Hadi proposed the Malay-Anglo school: integrating the positive elements of the Malay school with the English school for the benefits of the Malay students. In order to revitalize the society, al-Hadi emphasized that women’s education needed to be addressed urgently. Besides contributing to theoretical discussion, al-Hadi was also involved in various capacities in the establishment and management of several madrasahs: Madrasah Iqbal Islamiah, Madrasah al-Hadi dan Madrasah al-Masyhur. This study adopts the textual study approach in examining the relevant primary sources. At the same time, it connects the text with the larger socio-historical contexts, which shaped the production of ideas and text.